O movimento modernista como memórias de Mário de Andrade - Jobim, José Luís (2012)
This article aims to present “The Modernist Movement” as a Mário de Andrade memoirs, taking into account both the narrative of personal experiences of the author as a discursive genre and the issues his memoirs raises about his work.